Increased medical cost metrics for patients 50 years of age and older in the collaborate care model of treatment for depression. Issue 2 (27th April 2015) - Angstman, Kurt B.; Doganer, Yusuf C.; DeJesus, Ramona S.; Rohrer, James E.
Abstract: Background: The collaborative care model (CCM) has been consistently shown to achieve effectiveness in depression management compared to usual care. In the present study, we aimed to determine the impact of age on cost metrics in patients who were treated with CCM for 6 months after a diagnosis of depression. Methods: The upper quartile of age was 50 years and older ( n = 56), and the comparison group was composed of patients in the three younger quartiles, aged 18–49 years ( n = 163). Results: Patients in the older age group had an elevated median Current Procedure Terminology cost rank of 255.5 compared to 168.0 for the younger patients ( P < 0.001). Multiple logistic regression analysis revealed that being in the upper quartile of age (≥50 years) (odds ratio = 2.272, 95% confidence interval: 1.064–4.851; P = 0.034) and having higher numbers of clinical visits 6 months prior to index (odds ratio = 1.209, 95% confidence interval: 1.118–1.307; P < 0.001) were significant predictor variables of being cost rank outliers (>80th percentile) in patients with CCM. Conclusion: Medical cost utilization in the 6 months after diagnosis of depression was significantly higher in patients in the upper age quartile (≥50 years) enrolled in CCM than those in the lower quartiles (age <50).